2012
DOI: 10.1016/j.envpol.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a bioremediation process of PAHs in a PAH-contaminated soil at field and laboratory scales

Abstract: A laboratory experiment was carried on the same initial soil and at the same time than a windrow treatment in order to compare results at field and laboratory scales for a soil mainly contaminated with PAHs. After 6 months, laboratory experiments gave similar but less scattered results than those obtained in the field indicating that the field biotreatment was well optimised. The total amount of PAHs degraded after 6 months was ca. 90% and degradation rates followed a negative exponential trend. Relative degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 33 publications
2
41
0
1
Order By: Relevance
“…There have been a number of studies demonstrating the successful use of biopiling to remediate PAH contaminated soil. Lors et al [35] used large field scale windrows (5000 tons each) to remediate soils heavily contaminated with PAHs (3000 mg kg -1 ). After 181 days they reported 85% degradation of EPA 16 PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies demonstrating the successful use of biopiling to remediate PAH contaminated soil. Lors et al [35] used large field scale windrows (5000 tons each) to remediate soils heavily contaminated with PAHs (3000 mg kg -1 ). After 181 days they reported 85% degradation of EPA 16 PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…The losses of naphthalene from the soil columns are mainly attributed to volatilisation due to its elevated Henry's Law constant compared to the other tested PAHs. Park et al (1990) observed that volatilisation accounted for losses of 30% from two different soils under unsaturated conditions and Lors et al (2012) monitored the complete elimination of 2-ring PAHs in laboratory experiments conducted on PAH contaminated soils. There is also the possibility of microbial degradation as the soils were not sterilised and half-lives of the order of 2 days have been determined for naphthalene in soils (Park et al, 1990).…”
Section: Pah Distribution In the Soil Columnsmentioning
confidence: 99%
“…There is also the possibility of microbial degradation as the soils were not sterilised and half-lives of the order of 2 days have been determined for naphthalene in soils (Park et al, 1990). The potential for phenanthrene to undergo biodegradation is indicated by half-lives between 7 and 34 days with almost complete degradation (94%) in the soil environment after 3 months (Lors et al, 2012). The impact of biodegradation losses for phenanthrene in the soil column experiments is exemplified by the the total amounts retained at the end of the leaching experiment representing only 30.4 % (soil A) and 14.4 % (soil B) of that applied.…”
Section: Pah Distribution In the Soil Columnsmentioning
confidence: 99%
“…The lowest concentration of phenanthrene was obtained at a high level of macronutrients in the range of 67-87% and a low level of microelements (12-32%), where nitrogen was the dominant ingredient. The most effective biodegradation of phenanthrene proceeded in the following order N>K>P>Cl>Na>Mg [19][20][21].…”
Section: Application Of Chemical Compoundsmentioning
confidence: 99%